2017
DOI: 10.3389/fcimb.2017.00103
|View full text |Cite
|
Sign up to set email alerts
|

Colibactin Contributes to the Hypervirulence of pks+ K1 CC23 Klebsiella pneumoniae in Mouse Meningitis Infections

Abstract: Klebsiella pneumoniae is the most common pathogen of community-acquired meningitis in Taiwan. However, the lack of a physiologically relevant meningitis model for K. pneumoniae has impeded research into its pathogenesis mechanism. Based on the core genome MLST analyses, the hypervirulent K1 K. pneumoniae strains, which are etiologically implicated in adult meningitis, mostly belong to a single clonal complex, CC23. Some K1 CC23 K. pneumoniae strains carry a gene cluster responsible for colibactin production. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 50 publications
(68 reference statements)
3
71
1
1
Order By: Relevance
“…Colibactin damages DNA and disrupts the host cell cycle, but the exact mechanisms by which colibactin contributes to pathogenesis of hvKp are largely unknown. Genetic inactivation of colibactin synthesis in a pks + K1 ST23 isolate reduced the ability of this hvKP strain to colonize the gut and disseminate to other organs in a murine model of systemic infection as well as to induce cell death in the brain during meningitis [138]. Taken together, colibactin appears to support the colonization and pathogenesis of hvKp and may have contributed to the global spread of CG23 [112], of which K1 ST23 strains are prominent.…”
Section: Additional Hvkp Virulence Factorsmentioning
confidence: 93%
“…Colibactin damages DNA and disrupts the host cell cycle, but the exact mechanisms by which colibactin contributes to pathogenesis of hvKp are largely unknown. Genetic inactivation of colibactin synthesis in a pks + K1 ST23 isolate reduced the ability of this hvKP strain to colonize the gut and disseminate to other organs in a murine model of systemic infection as well as to induce cell death in the brain during meningitis [138]. Taken together, colibactin appears to support the colonization and pathogenesis of hvKp and may have contributed to the global spread of CG23 [112], of which K1 ST23 strains are prominent.…”
Section: Additional Hvkp Virulence Factorsmentioning
confidence: 93%
“…The regulators of the mucoid phenotype rmpA and rmpA2, which increase capsule production, also have been shown to increase hvKp virulence, perhaps by impairing phagocytosis and enabling survival within macrophages [9]. Additional hvKp-specific virulence factors identified include colibactin, which contributes to invasion of the central nervous system [10] and the putative metabolite transporter peg-344, which contributes to virulence in pulmonary infection models [11]. The mechanisms responsible for hvKp's relatively unique ability to infect multiple sites and metastatically spread are still poorly defined.…”
Section: The Emergence Of the Hypervirulent Klebsiella Pneumoniae Patmentioning
confidence: 99%
“…Recently, the pks gene cluster was also found in K pneumoniae . It was reported that pks ‐encoding colibactin was related to the K pneumoniae hypervirulence in meningitis model . On the basis of these researches, we speculated that there may be a potential correlation between the pks gene cluster, virulence, and K pneumoniae ‐induced bloodstream infections (BSIs).…”
Section: Introductionmentioning
confidence: 99%